Pelatihan Desain E-Modul Pengelolaan Kelas untuk Mendorong Literasi Digital Mahasiswa Pendidkan Guru Pendidikan Anak Usia Dini - Erdaliameta, Annisha; Fitriana, Laila (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
This community service activity aimed to enhance the digital literacy and pedagogical skills of PG-PAUD students through a workshop on designing classroom management e-modules. The one-day workshop emphasized hands-on practice, including concept introduction, demonstration of digital design applications, guided e-module creation, and evaluation through observation and participant reflection. Results indicate that participants improved their ability to operate digital tools, design structured classroom management content, and produce e-modules suitable for early childhood education. Reflections show that the workshop provided meaningful learning experiences, increased confidence in using technology, and motivated students to pursue further training. Overall, the activity effectively strengthened students’ digital competencies and preparedness as future early childhood educators.